Live birth rate is associated with oocyte yield and number of biopsied and suitable blastocysts to transfer in preimplantation genetic testing (PGT) cycles for monogenic disorders and chromosomal structural rearrangements. (October 2019) - Ben-Nagi, Jara; Jones, Benjamin; Naja, Roy; Amer, Ahmed; Sunkara, Sesh; SenGupta, Sioban; Serhal, Paul
Abstract: Objectives: To investigate whether live birth (LB) is associated with oocyte yield and number of biopsied and suitable blastocyst to transfer following preimplantation genetic testing (PGT) for monogenic disorders (PGT-M) and chromosomal structural rearrangements (PGT-SR). Study design: All couples underwent controlled ovarian stimulation, blastocyst biopsy, vitrification and transfer of suitable embryo(s) in a frozen embryo transfer (FET) cycle. Results: Of 175 couples who underwent PGT treatment, 249 oocytes retrievals were carried out and 230 FET were subsequently undertaken. 122/230 (53%, 95% CI 47–59) FET resulted in a LB and 16/230 (7%, 95% CI 4–11) have resulted in ongoing pregnancies. 21/230 (9%, 95% CI 6–14) FET resulted in miscarriage and 69/230 (30%, 95% CI 24–36) concluded with failed implantation. Two (1%, 95% CI 0–3) transfers underwent termination for congenital malformation, with no evidence of misdiagnosis by prenatal testing. The relationship between number of oocytes retrieved and number of blastocysts biopsied and suitable embryos to transfer were significant (p = 0.00; Incidence rate ratio (IRR) 1.05; 95% 1.04–1.06; p = 0.00; IRR 1.04; 95%, 1.03–1.06), respectively. The number of oocytes collected (p = 0.007; OR 1.06; 95% CI 1.01–1.10), the number of blastocysts biopsied (p = 0.001; OR 1.14; 95% 95% CI 1.06–1.23) and the number of suitable embryos to transfer (p = 0.00; OR 1.38; 95% CI 1.17–1.64) were all significantly associated with the odds of achieving a LB. There is a 14% and 38% increased chance of a LB per additional blastocyst biopsied and suitable embryo to transfer, respectively. Conclusions: PGT-M and PGT-SR outcomes are significantly associated with egg yield, number of blastocysts to biopsy and suitable embryos to transfer.